Rim Fracture of a Tibial Base-Plate Due to Retained Cement as a Cause of Catastrophic Failure of Unicompartmental Knee Arthroplasty: A Case Report. Issue 3 (July 2016) - Sawatzke, Alexander B.; Bollinger, Alexander J.; Butler, Paul D.; Roberts, Karl C.
Abstract : Case: We report a case of catastrophic implant failure due to fatigue fracture of a well-functioning unicompartmental knee arthroplasty at 7 years in an active 55-year-old man, who presented with sudden onset of atraumatic knee pain and effusion. The patient underwent revision to total knee arthroplasty. Intraoperative findings included a metallic fragment fractured off the rim of the tibial base-plate and cement retained in the tibial tray. Conclusion: Retained cement in the tibial tray resulted in increased tibial tray contact stresses and fatigue fracture of the rim of the tray, creating a free metallic loose body that produced symptoms.